Regulação dos veículos aéreos não tripulados para agricultura no Brasil: das competências normativas - Chiarello, Cássia Gilmara Fraga (2017)
This study aims to analyze the regulation of the use of unmanned aerial vehicles (vants) for agriculture in Brazil, presenting contributions to the legal regulation of this matter, based on the normative competencies of the federated entities and regulatory agencies. Based on the deductive method the development of this work is composed of three chapters. In the first part of the paper the fundamentals and the evolution of the use of such vehicles in the world are analyzed, highlighting the main concepts and issues that imply their regulation and applic ations, especially in the agriculture sector. In the second chapter, the regulation and draft laws in the country on vants, at the federal, state and municipal level, are analyzed, with emphasis on their application in the national agriculture sector, noting the scarcity of regulations as well as the limited scope of regulation In force. In the third chapter, proposals are evaluated that contribute to the regulation of unmanned vehicles, focused on agriculture in Brazil, in consideration of normative competencies. It identifies, therefore, the normative competences of the aviation to the agriculture, listing which organ has the attribution to legislate on the subject in the municipal, state and federal spheres. Afterwards, it examines the competence of the regulatory agencies, with special attention to the National Civil Aviation Agency (ANAC). It is concluded, listing the proposals for the regulation of use, based on the elements and actors involved in the process from the design of unmanned aircraft to its application in agriculture in Brazil..